Depleting fragile bodies: the political economy of sexual and reproductive health in crisis situations. Issue 4 (6th June 2018) - Tanyag, Maria
Abstract: In a crisis-prone world, the number of internally displaced persons (IDPs) uprooted by both armed conflicts and environmental disasters has drastically increased and displacement risks have intensified. Despite the growing attention within global security and development agendas to sexual and reproductive health and rights (SRHR), there remain striking gaps in addressing SRHR in crisis situations, particularly among IDP women and girls. This article examines the continuum between social reproduction in times of crisis and the material and ideological conditions that restrict women's bodily autonomy in everyday life. Using the case of the Philippines where millions of people are routinely affected by conflict and disaster-induced displacements, it argues that the failure to recognise the centrality of women's health and bodily autonomy not only hinders the sustainable provision of care and domestic labour during and after crisis, but also fundamentally constrains how security is enacted within these spaces. Thus, the article highlights an urgent need to rethink the gendered political economy of crisis responses as a building block for stemming gendered violence and depletion of social reproductive labour at the household, state, and global levels.